HADIS TARBAWI PERSPEKTIF TRIDHARMA PERGURUAN TINGGI - Moh. Mansur Fauzi (STAI Ma'had Aly Al-Hikam Malang, 2023)
Abstract: The Holy Qur’an and Hadith are the two main sources that shape Muslim culture and civilization. The problem is that there are still misunderstandings or misconceptions about the Al-Qur'an and Hadith, giving rise to a negative culture, such as terrorism under the guise of religion. The implication is that massive socialization is needed regarding the values ​​in the Al-Qur'an and Hadith. This article is the result of literature research which focuses on the theme of the Tarbawi Hadith or Education Hadith from the perspective of the three principles of Higher Education known as Tridharma Perguruan Tinggi. There are three findings of the article: 1) From an educational and teaching perspective, Hadith Tarbawi is a Basic Education Course (MKDK) which is generally taught at the Tarbiyah Faculty, such as in the Department of Islamic Religious Education (PAI) at UIN Raden Intan Lampung with a weight of 2 credits. 2) From a research and writing perspective, the Tarbawi Hadith can be actualized through the publication of written works, such as final course assignments (undergraduate thesis, master thesis, dissertation), scientific papers (essays, posters, articles) and books (monographs, textbooks, references). 3) From the perspective of community service, Hadith Tarbawi is transmitted to the community through preaching (da’wa) Hadith Tarbawi material, Hadith Tarbawi methodology training and Living Sunnah-based community service programs. Keywords: Hadith Tarbawi, Education Hadith, Three Principles, Tridharma Perguruan Tinggi. Abstrak: Al-Qur’an dan Hadis merupakan dua sumber utama yang membentuk budaya dan peradaban umat muslim. Problemnya, masih dijumpai salah paham atau paham yang salah terhadap Al-Qur’an dan Hadis, sehingga menimbulkan budaya negatif, seperti terorisme berkedok agama. Implikasinya, dibutuhkan sosialisasi masif terkait nilai-nilai dalam Al-Qur’an dan Hadis. Artikel ini merupakan hasil penelitian pustaka yang fokus pada tema Hadis Tarbawi atau Hadis Pendidikan dari perspektif tridharma perguruan tinggi. Temuan artikel ada tiga: 1) Dari perspektif pendidikan dan pengajaran, Hadis Tarbawi merupakan Mata Kuliah Dasar Kependidikan (MKDK) yang umumnya diajarkan di Fakultas Tarbiyah, seperti pada Jurusan Pendidikan Agama Islam UIN Raden Intan Lampung dengan bobot 2 SKS. 2) Dari perspektif penelitian dan penulisan, Hadis Tarbawi dapat diaktualisasikan melalui publikasi karya tulis, seperti tugas akhir perkuliahan (skripsi, tesis, disertasi), karya tulis ilmiah (esai, poster, artikel) dan buku (monograf, buku ajar, referensi). 3) Dari perspektif pengabdian kepada masyarakat, Hadis Tarbawi ditransmisikan kepada masyarakat melalui pelatihan metodologi Hadis Tarbawi, dakwah materi Hadis Tarbawi dan program pengabdian kepada masyarakat yang berbasis Living Sunnah. Kata Kunci: Hadis Tarbawi, Hadis Pendidikan, Tridharma Perguruan Tinggi.